2007
DOI: 10.1038/nature06064
|View full text |Cite
|
Sign up to set email alerts
|

Talc-bearing serpentinite and the creeping section of the San Andreas fault

Abstract: The section of the San Andreas fault located between Cholame Valley and San Juan Bautista in central California creeps at a rate as high as 28 mm yr(-1) (ref. 1), and it is also the segment that yields the best evidence for being a weak fault embedded in a strong crust. Serpentinized ultramafic rocks have been associated with creeping faults in central and northern California, and serpentinite is commonly invoked as the cause of the creep and the low strength of this section of the San Andreas fault. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
266
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(280 citation statements)
references
References 23 publications
12
266
0
2
Order By: Relevance
“…The δ 13 C data most likely indicate a source of carbon derived from organic-rich shales and permeable sandstones drilled in the lower sedimentary section of the SAFOD Main Hole. Moore and Rymer (2007) also observed that talc is forming as a result of the reaction of serpentine minerals with silica-saturated hydrothermal fluids that migrate up the fault zone. Therefore, for fault segments suspected to be particularly hazardous, the potential of their host lithology to produce metamorphic fluids should be evaluated in order to take into account the role of possible fluid infiltrations in triggering a seismic event.…”
Section: Metamorphic Fluid Sources Infiltrated From Below In the San mentioning
confidence: 95%
“…The δ 13 C data most likely indicate a source of carbon derived from organic-rich shales and permeable sandstones drilled in the lower sedimentary section of the SAFOD Main Hole. Moore and Rymer (2007) also observed that talc is forming as a result of the reaction of serpentine minerals with silica-saturated hydrothermal fluids that migrate up the fault zone. Therefore, for fault segments suspected to be particularly hazardous, the potential of their host lithology to produce metamorphic fluids should be evaluated in order to take into account the role of possible fluid infiltrations in triggering a seismic event.…”
Section: Metamorphic Fluid Sources Infiltrated From Below In the San mentioning
confidence: 95%
“…While the amount of deformation associated with the 3302-m shear zone is more pronounced than the Andreas Fault Zone (Solum et al, 2006). Moore and Rymer (2007) demonstrated that some of the serpentinite in the fault zone has been altered to talc, an unusual mineral in that it has exceptionally low frictional strength and is thermodynamically stable over the range of depths and pressures characteristic of the upper crust in this region. They speculated that if talc is widespread in the fault zone, it could explain both the strength of the fault and its creeping behavior.…”
Section: Downhole Measurementsmentioning
confidence: 99%
“…However, serpentinite minerals do not exhibit shear strengths weak enough to account for fault creep. Moore and Rymer (2007) identified talc-filled shears and veins from cuttings of the SAFOD borehole and suggested that interconnected films of talc would only require small volume fractions to attain the observed frictional weakness. Talc, derived as reaction product from silica-saturated hydrothermal fluids with serpentinite, is frictionally weak over wide pressure and temperature ranges (Figure 3b), and thereby creates an indirect association between serpentinite and fault creep.…”
Section: Earthquakes and Fault Creepmentioning
confidence: 99%
“…Because the veins and shears with which talc was found associated at SAFOD overprint all other textural features in the serpentinite grains, Moore and Rymer (2007) proposed that the talc is of recent origin. The decomposition of serpentinite with silica-saturated fluids (possibly derived from a deeper fluid source) to talc is a dehydration reaction and releases additional water into the system .…”
Section: Earthquakes and Fault Creepmentioning
confidence: 99%